Some Cordial Labeling on Human Chain Graph - Anitha, K; Selvam, B; Thirusangu, K (International Journal of Computer Sciences and Engineering, 2025)
A Human chain graph is a simple, finite and undirected geaph. In this paper, we prove that the existence of Vcordial and Homo-cordial labeling for the Human chain graph by using algorithms